63.7k views
4 votes
(17)^ 3 *(289)^ -6 =(17)^ 2m - 1​

User Alex Aung
by
6.1k points

1 Answer

3 votes

Answer:

m = -4

Explanation:

The given expression is :


(17)^(3)\cdot(289)^(-6)=(17)^(2m-1)

We need to find the value of m

We know that, 17² = 289

So,


(17)^(3)\cdot(17^2)^(-6)=(17)^(2m-1)\\\\(17)^(3)\cdot(17)^(-12)=(17)^(2m-1)

Also,
x^ax^b=x^(a+b)

So,


17^(3-12)=17^(2m-1)\\\\17^(-9)=17^(2m-1)\\\\\implies -9=2m-1\\\\-9+1=2m\\\\-8=2m\\\\m=-4

So, the value of m is equal to -4.

User Juan Fontes
by
6.1k points